2023
DOI: 10.1177/24741264231200739
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Cystoid Macular Edema in Silicone Oil–Filled Eyes

Abdulla Shaheen,
James Lai,
Maria Magraner
et al.

Abstract: Purpose: To investigate the clinical outcome of cystoid macular edema (CME) in eyes undergoing silicone oil (SO) tamponade with subsequent SO removal (SOR). Methods: A retrospective case series of adult patients with CME treated with SO tamponade and SOR was conducted between January 2015 and January 2021. Exclusion criteria included eyes with a prior SO tamponade, those that did not undergo SOR, or those with infectious/inflammatory diagnoses. The primary outcomes were the incidence and resolution rates of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Shaheen et al 2 present the Bascom Palmer Eye Institute experience with cystoid macular edema (CME) in the setting of retained silicone oil and note the difficulty with its treatment and the potential for persistent CME even after silicone oil removal.…”
Section: In This Issuementioning
confidence: 99%
“…Shaheen et al 2 present the Bascom Palmer Eye Institute experience with cystoid macular edema (CME) in the setting of retained silicone oil and note the difficulty with its treatment and the potential for persistent CME even after silicone oil removal.…”
Section: In This Issuementioning
confidence: 99%
“…The authors reported that ME resolved in 10 eyes, seven of which occurred after SO removal. They also highlighted that eyes with PVR had a higher rate of persistent ME [46]. Er et al investigated 65 eyes, which were divided into three groups based on the duration of silicone tamponade: ≤3 months, 3-6 months, and ≥6 months.…”
Section: Incidencementioning
confidence: 99%